Access to Financial Services in Zambia - de Luna Martínez, José (World Bank, Washington, DC, 2012)
Despite the deep financial sector reforms undertaken in Zambia in the early 1990s, the expected benefits of establishing a market-based banking system has not materialized. In 2005 the banking system continued to be small and underdeveloped. Credit to the private sector by banks represented only 8 percent of GDP in 2005, which is slightly lower than the level registered in 1990. As in the early 1990s, only large corporations and a few small- and medium-size enterprises have access to credit in 2006. Moreover, less than 8 percent of Zambia's adult population had a bank account in 2005. And despite the open door policy to foreign financial institutions, which has been in place since Zambia's independence, only a few new banking products have been introduced by foreign banks to serve the needs of households and firms. This paper analyzes the factors that have prevented the development of a large and inclusive banking system in Zambia and highlights possible actions that may help improve access to finance in Zambia in both the short and long terms.